Anisotropy, size, and aspect ratio effects on micropillar compression of AlSiC nanolaminate composites. (1st August 2016) - Mayer, C.R.; Yang, L.W.; Singh, S.S.; Llorca, J.; Molina-Aldareguia, J.M.; Shen, Y.L.; Chawla, N.
Abstract: Metal-ceramic nanolaminate composites show promise as high strength and toughness materials. Micropillar compression was used to characterize the mechanical behavior of AlSiC multilayers in different orientations including loading at 0°, 45° and 90° with respect to the direction of the layers. The 0° orientation showed the highest strength while the 45° orientation showed the lowest strength. Each orientation showed unique deformation behavior. Effects of pillar size and aspect ratio were also studied. Higher compressive strengths were observed in smaller pillars for all orientations. This effect was shown to be due to a lower probability of flaws using Weibull statistics. Additionally, changes in the aspect ratio was shown to have no significant effect on the behavior except an increase in the strain to failure in the 0° orientation. Finite element analysis (FEA) was used to simulate and understand the effect of these parameters on the deformation behavior. Graphical abstract: